1992
DOI: 10.1039/dt9920003403
|View full text |Cite
|
Sign up to set email alerts
|

Use of Michael additions to (Ph2P)2CCH2complexes to prepare thiophene- and pyrrole-functionalised metal–phosphine complexes

Abstract: The complex [Pd(O,CMe),(vdpp)]1 a [vdpp = (Ph,P), C=CH,] undergoes nucleophilic addition at the double bond with primary alcohols to afford [Pd(O,CMe),{(Ph,P),CHCH~OR}] 2 [R = Me, Et, CH,CH,C,H,S-3 or CH,C6H,(OMe),-3,4]. These were not isolated pure, but metathesis with Nal gave the corresponding diiodides 3, which were isolated, and have been fully characterised by microanalysis and infrared and NMR ('H and 31P-(1H}) spectroscopies. By using 2-(3-thieny1)ethanol as the nucleophile, the complex [Pdl,{( Ph,P)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The addition of nucleophiles to the double bond of chelated (Ph 2 P) 2 CCH 2 has been demonstrated as a route to coordinated, functionalized diphosphines of the type (Ph 2 P) 2 CHCH 2 X ( X = −NHR, −NR 2 , −OR, −C⋮CR, etc. ), and we have used this reaction to prepare redox-active Ru II complexes for oxide surface modification 26 and for incorporation into conjugated polymers …”
mentioning
confidence: 99%
“…The addition of nucleophiles to the double bond of chelated (Ph 2 P) 2 CCH 2 has been demonstrated as a route to coordinated, functionalized diphosphines of the type (Ph 2 P) 2 CHCH 2 X ( X = −NHR, −NR 2 , −OR, −C⋮CR, etc. ), and we have used this reaction to prepare redox-active Ru II complexes for oxide surface modification 26 and for incorporation into conjugated polymers …”
mentioning
confidence: 99%
“…Although the double bond in uncoordinated vinylidenebis(diphenylphosphine) is not normally susceptible to nucleophilic attack, it has been shown that complexation to a metal center activates the double bond in such a manner that various nucleophiles can be added by Michael-type reactions. In these processes, the nucleophile HNu is added to complexes [M]−(PPh 2 ) 2 CCH 2 to give the products [M]−(PPh 2 ) 2 CH−CH 2 Nu. However, reactions in which the addition takes place only at the terminal carbon atom of the double bond, thus affording species of the type [M]−(PPh 2 ) 2 C−CH 2 Nu in which the central carbon atom can be regarded as a methanide carbon, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Pd II , Pt II , Pt IV ) than by co-ordination to M 0 (M = Cr, Mo or W). 5, 6 It was therefore of interest to investigate the co-ordination chemistry of 2,3-dpppn with Pd II , Pt II and Ru II , and to investigate whether the co-ordinated ligand would undergo nucleophilic addition. In this paper, we report the syntheses and characterisation of neutral and cationic 2,3-dpppn complexes of these metals, and some chemistry of the coordinated ligand.…”
mentioning
confidence: 99%